Neoadjuvant sintilimab and chemotherapy for resectable esophageal squamous cell carcinoma: a phase II clinical trial - Guo, Jincheng; Qiao, Chengrui; Lu, Jiabin; Yang, Shiqing; Zhang, Boyi; Tang, Dongxia; Pang, Hui (Frontiers in Immunology, 2025)
BackgroundCombination of anti-PD-1 monoclonal antibody with chemotherapy has been widely used as a first-line treatment for metastatic esophageal squamous cell carcinoma (ESCC). However, the efficacy of this therapeutic combination as a neoadjuvant intervention for resectable ESCC remains inadequately explored. This study aims to evaluate the efficacy and safety of sintilimab in combination with chemotherapy as a neoadjuvant therapy for ESCC.MethodsIn this single-arm, phase II study, patients with histopathologically diagnosed resectable ESCC who had clinical cT1-3/N0-1M0 (stage II-III) were recruited. Sintilimab (200mg, iv, d1) in combined with chemotherapy (nab-paclitaxel 260 mg/m2, d1 and cisplatin 75 mg/m2, d1-3) were administered every 3 weeks for 2 cycles. The primary endpoint was pathological complete response (pCR).ResultsFrom November 2020 through November 2022, 29 patients were enrolled and 27 completed the two cycles of neoadjuvant therapy. A total of 21 patients underwent surgery. The pCR rate was 28.6% (6/21) and the major pathologic response (MPR) rate was 42.9% (9/21). The most common Grade 3 or 4 treatment-related adverse events were leukopenia (26.7%) and neutropenia (20%). No delays in surgical procedures or unexpected surgical complications attributable to the treatment were reported.ConclusionsThe combination of sintilimab and chemotherapy as a neoadjuvant regimen was tolerable and associated with favorable responses for ESCC patients. Given these favorable results, this regimen could serve as a viable alternative in the neoadjuvant treatment landscape for ESCC, with particular applicability to Chinese patient populations.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2000040345.